The Bio-Physiological and Socio-Economic Profile of Mutrashmari Patients - Suden , Akshay (International Research Journal of Ayurveda & Yoga, 2020)
in the suburbs of Jammu ( Jammu & Kashmir State ) to assess the comparative efficacy of Kullutha(K), Shwet Parpati(SP) – a mineral compound, singly as well as jointly i.e. K+SP, to evaluate their effects on a random sample of ten mutrashmari patients allocated to each in 2012-13. This article presents the bio-physiological and socio-economic profile of the sample patients as follows Seventy percent of the cases were in the 3rd and 4th decades i.e. 21– 40 years age band. The gender ratio was : Female : Male : : 1: 1.72. Eighty-three percent were Hindu and the rest were Muslim. About 73.3 had rural background and the rest 26.7 % were from urban areas. Occupationally, 66.7 % belonged to the working class viz. farming (43.4%) and labour (23.3%). Seventy percent cases were either Higher Sec. pass are above and only 80.0 % of them were married. The lower socio-economic classes made up 63.0% of the sample. Only 16.6 % and 10. 0 % belonged to sthenic and pthisical categories respectively. The patients belonging to pthisical and other sicknesses were in the first stage i.e. curable and were on treatment. Addiction to tea was 100 %, tobacco chewing and smoking 70 % each and alcohol 66.7 % . Fifty per cent cases reported disturbed sleep while 46.7 % reported normal sleep. Fifty percent of the cases consumed